Usability questionnaire for standalone or interactive mobile health applications: a systematic review - Phei Ching Lim; Yen Li Lim; Retha Rajah; Hadzliana Zainal (BMC Digital Health)
Abstract Background Mobile health apps (mHealth apps) play important roles in various aspects of disease management, health monitoring, behavioural change, education, and medication adherence. The usability and satisfaction of the app indicate whether the app is favoured and used for its optimal potential. Surveys are among the most commonly used methods and are simple to conduct, and data analysis is easily quantifiable. We aimed to synthesize the evidence from questionnaires available to assess the usability and satisfaction of mHealth apps, both standalone and interactive apps, and to evaluate the validation status of the questionnaire. Methods An extensive search of the literature published from 2000 to June 2023 was conducted via PubMed, Scopus and Google Scholar. The keywords, MeSH terms, truncation and text words used for the search included “mobile health” or “health” or “mobile app*” or “mhealth” and “patient satisfaction” or “user” or “usability” or “feasibility” and “survey” or “questionnaire”. Eligibility was independently assessed by two investigators on the basis of the inclusion and exclusion criteria. Human studies published in English that reported the usability and/or satisfaction of patients or users with mHealth apps with published questionnaires were included. Studies that did not include questions or assessed the usability and/or satisfaction of healthcare providers or experts were excluded. Studies such as questionnaire development and validation, translation studies, qualitative studies, reviews, editorials, brief reports, comments, conference proceedings, letters and wrong outcomes were excluded. The first author, year and country of publication; sample size; demographics of the study population; name and type of mobile health application; assessment tool; validation status; and number of questions, domains and scores were collected from each study. The quality assessment was independently performed by two reviewers via the Joanna Briggs Institute (JBI) critical appraisal checklist for cross-sectional studies. Results Electronic database searches identified 5703 potentially relevant studies, and 40 studies with a total of 1552 respondents were included. The majority of the studies assessed the usability of standalone apps (62.5%). Half of the studies (50.0%) utilized researcher-developed questionnaires, whereas only 25% of the researcher-developed questionnaires were validated. Nine studies used the System Usability Survey (SUS). The majority of the studies (70.0%) used questionnaires that were not validated. When the JBI critical appraisal checklist was used to assess quality, 14 (35.0%) studies were assessed to be poor quality. Conclusion Researchers have developed questionnaires, and the SUS is the most commonly used method to assess the usability and satisfaction of mobile health applications. Although most questionnaires have not been validated, ensuring the optimal use of mHealth apps via adapted and customized questionnaires is crucial.